Sub-antimicrobial doses of doxycycline decreased bone loss related to ligature-induced periodontitis in hypertensive rats - Vieira, Gustavo H.A.; Messora, Michel R.; Moura, Janine M.T.; Fernandes, Patricia G.; Furlaneto, Flávia A.C.; Palioto, Daniela B.; de Souza, Sérgio L.S.; Novaes, Arthur B.; Gerlach, Rachel F.; Silva, Cristina A. [UNESP]; Taba, Mario (Elsevier, 2019)
Background/Objective: The beneficial effects of sub-antimicrobial dose doxycycline (SDD) associated with nonsurgical periodontal therapy are well documented. Recently, the effects of SDD on metalloproteinases have been investigated in the treatment of hypertension. The aim of this study was to evaluate the effects of SDD on ligature-induced periodontitis in spontaneously hypertensive rats (SHR). Methods: Fifty-four adult male rats were divided into three groups: SHR-C, SHR-L and SHR-L-DOX (C - Control; L – Ligature). In group SHR-L-DOX, animals were treated with daily 5 mg/kg SDD administration. In L groups, a ligature remained around mandibular first molars for the first 10 days. Each group was divided for euthanasia at 10 or 21 days. Microtomographic and histometric analyses were performed. Osteoclastogenesis was evaluated by tartrate-resistant acid phosphatase (TRAP) assay and gene expression of 84 inflammatory mediators by polymerase chain reaction (PCR) array. Results: Group SHR-L-DOX presented reduced systolic blood pressure when compared with group SHR-L at both 10 and 21 days (p < 0.05). Group SHR-L-DOX showed decreased bone and attachment loss in comparison with group SHR-L at both 10 and 21 days (p < 0.05). SDD treatment reduced the amount of TRAP-positive cells at 10 days (p < 0.05). Group SHR-L-DOX showed a downregulated inflammatory genes profile in comparison with SHR-L at 10 and 21 days. Conclusion: SDD therapy exerted systemic modulatory effect on inflammation with reduced periodontal tissue destruction in hypertensive rats.
Keywords: Cardiovascular disease(s); Gene expression; Host modulation therapy; Periodontitis